Transformational Islamic Leadership as a Strategic Approach to Organizational Change in Islamic Education - Muhammad Sodiqul Fikri; Nadia Putri Kamila; Sabila Qurrota A’yun; Eti Hadiati; Inamul Azad (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
This study examines the role of Transformational Islamic Leadership in managing organizational change within Islamic educational institutions by analyzing how core Islamic leadership values—amanah (trustworthiness), justice, shura (consultation), and ukhuwah (brotherhood)—can be integrated with transformational leadership dimensions to support effective organizational transformation. This research employs a systematic literature review method by analyzing 25 peer-reviewed journal articles published within the last five years. The articles were selected based on relevance, quality, and alignment with the themes of Islamic leadership and organizational change, and were examined using thematic analysis to identify recurring patterns and conceptual relationships. The findings indicate that integrating Islamic leadership principles with transformational leadership dimensions-idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration-enhances teacher motivation, engagement, and professional development. However, challenges such as limited managerial support and cultural resistance remain barriers to effective implementation. This study contributes by proposing a conceptual framework that synthesizes Islamic leadership values with contemporary transformational leadership theory as a structured guide for organizational change in Islamic education, and it recommends future empirical studies to validate the framework across diverse educational contexts.